Scientific approaches to rational utilization of small-sized pacific saury С ol о labis saira in canning industry - Tatyana A. Davletshina; Lidiya V. Shulgina; Nadezhda V. Dolbnina; Zinaida P. Shvidkaya; Galina I. Zagorodnaya; Elena A. Solodova; Konstantin G. Pavel (Известия ТИНРО)
Parameters of food safety and food and biological value are tested for muscular tissue of small-sized pacific saury stored under temperature of minus 30 °C and minus 18 °C. The muscular tissue contains 21.0-22.1 % of proteins and 10.6-11.8 % of lipids. Quality of the raw material after the storage corresponds to all hygienic and sanitary requirements, moreover, the rate of histamine decreasing and lipids oxidation and hydrolysis allows to prolong the time of frozen storage under temperature minus 30 °C up to 6 months. The most rational utilization of the small-sized saury is its processing to canned pate. Food and biological value of the canned pate is evaluated, regime of its sterilization is scientifically substantiated. Technology and recipe of the canned food «Pate Special of pacific saury» is developed. The product is distinguished by high content of polyunsaturated fatty acids of series ω6 and ω3 in the ratio 3.4 : 1.0, so it can be considered as the product of preventive nutrition .